Consequences of use of anabolic androgenic steroids - Casavant, M. J.; Blake, K.; Griffith, J.; Yates, A.; Copley, L. R. M (Pediatric Clinics of North America, 2007)
Whether providing anticipatory guidance to the young adolescent patient, conducting a preparticipation examination on a young athlete, or treating a sick user of anabolic androgenic steroids (AASs), the primary care physician must be familiar with the adverse consequences of the use of these compounds. This article reviews the endocrine, cardiovascular, neuropsychiatric, musculoskeletal, hematologic, hepatic, and miscellaneous effects of AASs, highlighting effects reported in children and adolescents, and relying on consequences in adults when pediatric data is unavailable.